Cross-country differences in entrepreneurial internationalization tendencies: Evidence from Germany and Pakistan - Laura H. Middermann; Lubna Rashid (Administrative Sciences, 2019)
Previous research has emphasized the importance of entrepreneurial characteristics for international entrepreneurship, hence the application of concepts such as entrepreneurial orientation and global mindset to the study of entrepreneurial internationalization tendencies (EIT). However, literature does not adequately address how EIT differ between countries or manifest in fragile country settings. We address this gap through a quantitative study to investigate EIT in two national settings that largely differ in terms of development, institutional stability, and culture. Through the lens of the institutional theory and the mindset theory, we therefore piloted the study on 112 high-growth startups in Germany and Pakistan. Our findings show, that while entrepreneurs in Germany and Pakistan show comparable levels of innovativeness and proactiveness, they significantly differ in other EIT measures. German entrepreneurs appear to have higher levels of risk-taking, which when explained through the institutional theory lens can be attributed to the higher institutional stability and support as well as social security in Germany. This potentially makes engagement in risky activities, such as business internationalization, more appealing than in Pakistan. However, despite having lower international cognition and international knowledge compared to Germany, Pakistani entrepreneurs appear to exhibit higher degrees of international behavior.
Keywords: 350; international entrepreneurship; emerging markets; cross-country; entrepreneurial orientation; global mindset; institutional theory; mindset theory; entrepreneurial cognition